2017
DOI: 10.1016/j.bbrc.2017.03.043
|View full text |Cite
|
Sign up to set email alerts
|

MiR-126 impairs the intestinal barrier function via inhibiting S1PR2 mediated activation of PI3K/AKT signaling pathway

Abstract: MiR-126 down-regulated S1PR2 and then prevented the activation of PI3K/AKT signaling pathway, which ultimately could damage intestinal mucosal barrier function.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 12 publications
2
22
0
Order By: Relevance
“… 33 , 34 Expression of miR-126 has been previously shown to be higher in IBD biopsies than controls, and miR-126 overexpression contributes to intestinal mucosal barrier dysfunction in vitro. 35 Lastly, miR-126 has been shown to downregulate expression of Iκβα, an important inhibitor of NF-κB signaling pathway. 36 …”
Section: Discussionmentioning
confidence: 99%
“… 33 , 34 Expression of miR-126 has been previously shown to be higher in IBD biopsies than controls, and miR-126 overexpression contributes to intestinal mucosal barrier dysfunction in vitro. 35 Lastly, miR-126 has been shown to downregulate expression of Iκβα, an important inhibitor of NF-κB signaling pathway. 36 …”
Section: Discussionmentioning
confidence: 99%
“…Various studies have reported that GRb1 protects against the IR-induced injury of numerous organs, including the heart and kidneys (37,38). Additionally, activation of the PI3K/Akt pathway attenuates injury and alleviates damage to organs, such as the intestine and lungs (39,40). The effects of GRb1 on IIR injury and the underlying mechanisms have not yet been fully investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, IκB, an inhibitor of NFκB, is a downstream target of miR-126-3p and the transfection of a miR-126-3p mimic decreases the expression of IκB in a dose-dependent manner [48]. MiR-126 also impairs intestinal mucosal barrier function under LPS stimulation by targeting S1PR2 through the PI3k/AKT signaling pathway [49]. Functional experiments are required to further clarify its role in axSpA.…”
Section: Discussionmentioning
confidence: 99%